Risk factors for the environmental spread of different multidrug-resistant organisms: a prospective cohort study. (May 2021) - Saliba, R.; Ghelfenstein-Ferreira, T.; Lomont, A.; Pilmis, B.; Carbonnelle, E.; Seytre, D.; Nasser-Ayoub, E.; Zahar, J.-R.; Karam-Sarkis, D.
Summary: Background: Substantial scientific evidence shows that contamination of environmental surfaces in hospitals plays an important role in the transmission of multidrug-resistant organisms (MDROs). To date, studies have failed to identify the risk factors associated with environmental contamination. Aim: To evaluate, compare, and identify factors associated with environmental contamination around carriers of different MDROs. Methods: This was a prospective cohort study from May 2018 to February 2020. A total of 125 patients were included, having been admitted to Avicenne Hospital and Hotel Dieu de France de Beyrouth Hospital who were faecal carriers of MDROs (extended-spectrum β-lactamase-producing Enterobacterales (ESBL-PE), carbapenemase-producing Enterobacterales (CPE), vancomycin-resistant enterococci (VRE)). For each patient, quantification of MDRO in stool was undertaken, plus a qualitative evaluation of the presence of MDRO in six different environmental sites; and clinical data were collected. Findings: MDROs comprised ESBL-PE (34%), CPE (45%), and VRE (21%). The most frequent MDRO species was Escherichia coli . Contamination of at least one environmental site was observed for 22 (18%) patients. Only carriage of VanA was associated with a significantly higher risk of dissemination. Having a urinary catheter, carriage of OXA48 and E. coli were protective factors against environmental contamination. There were no significant differences in environmental contamination between E. coli and other Enterobacterales or between ESBL-PE and CPE. Conclusions: Hospital environmental contamination rates are substantially higher for patients with VRE, compared to the low environment dissemination rates around ESBL-PE and CPE. Further studies on a larger scale are needed to confirm the validity of our findings.